Adaptive robust control of marine vehicles with periodic disturbance compensation: an observer-based output feedback approach - Kurtoglu, Deniz; Bidikli, Baris; Tatlıcıoğlu, Enver; Zergeroğlu, Erkan (Springer Japan Kk, 2022)
This work concentrates on output feedback trajectory tracking control of marine vehicles with dynamical uncertainties. The system under consideration, due to the natural response of oceanic waves, is also subject to periodic external disturbances. The output feedback structure of the proposed controller algorithm is established via a novel nonlinear model-free observer in conjunction with a Fourier series expansion-based periodic disturbance estimator. Lyapunov-based arguments have been utilized to prove the stability of the closed loop system and the convergence of tracking and unmeasured state observation errors under the closed loop operation. Performance demonstration and viability of the proposed method are realized via comparative numerical simulations.
Keywords: Marine vehicles; Robust adaptive control; Output feedback; Tracking control